Social, Economic and Environmental Sustainability of Hydroelectric Power Plant: A Literature Review - Motalib, Jalaloden (Journal of Interdisciplinary Perspectives, 2023)
Hydroelectric power plants are increasingly regarded as a viable source of sustainable renewable energy in various countries, including the Philippines, given its extensive archipelagic landscape. Despite their pivotal role, there is a notable scarcity of research on the sustainability aspects of hydroelectric power plants. This study aimed to assess the impact of hydroelectric power plants on the lives of residents in the Philippines by examining their social, economic, and environmental dimensions. The research employed a literature review that scrutinized existing scientific literature about the social, economic, and environmental sustainability of hydroelectric power plants. Content analysis was utilized to categorize articles based on content grouping, encompassing topics such as the water quality of Lake Lanao, sustainability variables, and the overarching policies of the Philippine government concerning the sustainability of hydropower dams. The literature review revealed adverse effects of hydroelectric power plants, particularly on the social, economic, and environmental aspects associated with these projects. Concerns were identified, ranging from issues related to the water quality of Lake Lanao and the river to the lack of adequate waste management systems among residents. Compounding these challenges were forced evictions and a reduction in job opportunities, resulting in a diminished contribution to industrial processes. These findings underscore the urgent need for a comprehensive examination of the Agus Phase 1 Hydroelectric Power Plant, considering all three major variables—social, economic, and environmental—in the context of policy modification.